The risks associated with using a mobile phone by young drivers - Čubranić-Dobrodolac, Marjana; Čičević, Svetlana; Dobrodolac, Momčilo; Nešić, Milkica (Transport, 2013)
A substantial body of research has shown that mobile phone usage could lead to the impairment of driving performance and increase the likelihood of driving accidents. The use of mobile phone while driving is a major problem for inexperienced drivers. The reason for this lies in the fact that they have not developed abilities to process different types of information simultaneously. Mobile phone use may result in reduced attention allocation to the various tasks during driving. The research of young drivers’ habits related to mobile phone usage while driving is presented in this paper. A series of questions were administered, including along with demographic measures, self-reported number of traffic accidents and several kinds of driving behaviour such as alcohol consumption. The results have shown that 68% of young drivers used mobile phone while driving. Additionally, a relationship was found between frequency of mobile phones usage and the number of traffic accidents, consequences of traffic accidents, as well as, driving under the influence of alcohol. The general conclusion could be drawn that young drivers choose their preferred driving style, safe or unsafe. If they are unsafe drivers, they combine various types of unsafe behaviour, the same stands for a safe driving style as well. First Published Online: 24 Dec 2013